SUBTITLING AND DUBBING AS ADEQUATE METHODS OF AUDIOVISUAL TRANSLATION. - Akhmedova Malikakhon Tolibjon qizi (TADQIQOTLAR.UZ, 2024)
Annotation: In the global era, translation process is encountered at every stage of our life including social sites and media. These days most of the media products, such as, movies, TV series, animations and even songs are being translated much more than before; these translations are displayed by subtitles and dubbing. However, to interpret the given material from source language to target language is far from easy. Namely, preparing materials for subtitling and dubbing is sophisticated process and in this case translator may experience various complicated conditions. This article presents specific information about commonly used modes of audiovisual translation: subtitling and dubbing, as well as, it proposes some translation techniques and strategies in order to make subtitling and dubbing process fluently.